Hypomagnesemia in dairy cattle in Uruguay - Doncel,Benjamín (2019)
ABSTRACT: An outbreak of hypomagnesemia is reported in Holstein dairy cattle grazing lush oat (Avena sativa) pasture in Uruguay. Nine of 270 (3.3%) cows died in May-July (autumn-winter) 2017. These nine cows were from 2 to 9-years-old (1st-6th lactation), with 22 to 194 days of lactation and 15.8 to 31.4L of daily milk production. Two cows with acute sialorrhea, muscle spasms, lateral recumbency, weakness, opisthotonos, and coma, were euthanized and necropsied. No significant macroscopic or histological lesions were found. One untreated clinically-affected cow and eight out of 14 clinically healthy cows of the same group under similar management and production conditions had low serum levels of Mg (lower than 0.7mmol/L). Secondarily, both clinically affected cows and six out of 14 healthy cows had low serum Ca levels. The K/(Ca+Mg) ratio of two oat forages, corn silage, and ration was 5.10, 7.73, 2.45, and 0.85, respectively. A K/(Ca+Mg) ratio lower than 2.2 represents a risk for hypomagnesemia. The difference between the contribution-requirement of minerals in the diet was established and a daily deficiency of Mg (-0.36g/day), Na (-25.2g/day) and Ca (-9.27g/day) was found, while K (184.42g/day) and P (12.81g/day) were in excess. The diet was reformulated to correct the deficiencies and the disease was controlled by the daily administration of 80g of magnesium oxide, 80g of calcium carbonate and 30g sodium chloride per cow. It is concluded that hypomagnesemia is a cause of mortality in dairy cattle in Uruguay, and that the condition can be prevented by appropriate diet formulation.